FEATURES OF DOMESTIC, INBOUND AND OUTBOUND TOURISM IN CENTRAL ASIA - F. K. Saidova; B. T. Muhsinov (Galaxy International Interdisciplinary Research Journal, 2022)
The article describes the specifics of domestic, inbound and outbound tourism in Central Asia, the internal and external capabilities of countries, as well as ways to achieve sustainable tourism development in Uzbekistan.